Interprofessional education—situations of a university in Hong Kong and major hurdles to teachers and students - Li, Joyce T. S.; Chau, Janita P. C.; Wong, Samuel Y. S; Lau, Ann S. N.; Chan, Wallace C. H.; Yip, Peggy P. S.; Yang, Yijian; Ku, Fred K. T.; Sze, Felix Y. B.; King, Irwin K. C.; Lee, Vivian W. Y. (Frontiers in Education, 2022)
Studies have provided evidence that Interprofessional Education (IPE) can improve learners’ attitudes, knowledge, skills, behaviors, and competency. Traditionally, IPE is commonly seen in the healthcare professional training in tertiary education. Aging is a global issue that requires more than just a single healthcare sector. It requires interdisciplinary collaboration and understanding to tackle the issues. Therefore, IPE is essential for nurturing university students to tackle the ever-changing global challenges. In addition, different hurdles can hinder IPE development. To have a better understanding of the feasibility, acceptance, and educational value of IPE in Hong Kong, we conducted a cross-sectional quantitative study. We invited teachers and students from a Hong Kong university to fill in an online survey that evaluated their understanding and participation in IPE, their attitude toward IPE, and the barriers to developing IPE from March to June 2020. Among the 37 academic staff and 572 students who completed the survey, 20 (54.1%) teachers and 422 (73.8%) students had never heard of IPE before, and 26 (70.3%) teachers and 510 (89.2%) students had never participated in any IPE activities. Major barriers reported by teachers included an increase in teaching load (72.9%), lack of administrative support (72.9%), lack of financial support and limited budget (67.5%), difficulty to make logistic arrangements (64.8%), and problems with academic schedules and calendars (62.1%). The survey findings revealed that despite the positive attitude of university teachers and students toward IPE, barriers that could hinder the development of IPE included heavy teaching and administrative load and logistic arrangement for classroom arrangement and academic scheduling involving multiple faculties.